Discovery of Functional Antibodies Targeting Ion Channels. (April 2015) - Wilkinson, Trevor C. I.; Gardener, Matthew J.; Williams, Wendy A.
Ion channels play critical roles in physiology and disease by modulation of cellular functions such as electrical excitability, secretion, cell migration, and gene transcription. Ion channels represent an important target class for drug discovery that has been largely addressed, to date, using small-molecule approaches. A significant opportunity exists to target these channels with antibodies and alternative formats of biologics. Antibodies display high specificity and affinity for their target antigen, and they have the potential to target ion channels very selectively. Nevertheless, isolating antibodies to this target class is challenging due to the difficulties in expression and purification of ion channels in a format suitable for antibody drug discovery in addition to the complexity of screening for function. In this article, we will review the current state of ion channel biologics discovery and the progress that has been made. We will also highlight the challenges in isolating functional antibodies to these targets and how these challenges may be addressed. Finally, we also illustrate successful approaches to isolating functional monoclonal antibodies targeting ion channels by way of a number of case studies drawn from recent publications.